Evaluation of students’ perceptions and feedback about teaching-learning pharmacology in a medical college of central Nepal - Bhurtyal, Karma Murti; Karki, Sirisa; Paudel, Gita; Baral, Sanjay Raj; Gautam, Ashish; Chaurasia, Roshan Kumar; Khanal, Unisha (Journal of Chitwan Medical College, 2022)
Background: Learners’ feedback is considered an effective tool in evaluating teaching-learning methods and revising curriculum. The aim of the present study was to assess perception and feedback of undergraduate medical students towards teaching-learning pharmacology. Methods: This was a descriptive cross-sectional questionnaire-based study conducted among 183 undergraduate medical students of Chitwan Medical College, Chitwan Nepal from March 2021 to April 2021.. Perception and feedback of students towards teaching-learning pharmacology was assessed using a pretested and validated questionnaire. Results: More than half (53.6 %) of the students reported pharmacology as their favorite subject, but only 27.4 % students would opt to pursue post-graduation in the same subject. Majority of the students opined a review of curriculum was necessary with inclusion of recent advances (86.4 %) and emphasis on national health problems (83 %) with a change in assessment (inclusion of multiple choice questions) (83 %). Liquid-crystal display (LCD) projector and whiteboard combined was chosen as the ideal teaching-learning media and group discussion as the ideal teaching-learning method by 85.2 % and 53.6% of students respectively. Majority of the students suggested more use of audio-visual aids (94.5%) and inclusion of case-based learnings (98.9 %) into the curriculum. Conclusions: Perception of students towards teaching-learning pharmacology was positive. A review of the current curriculum with inclusion of a new assessment tool was suggested.